(untitled) (Global Conference on Medical and Health Sciences, 2026)
Despite a decline in the share of small business in GDP, it continues to play a decisive role in regional economies, employment, and the service sector. Analytical assessments indicate the necessity of developing small entrepreneurship based on regional specialization. At the same time, ensuring state support, financial facilitation, and competitive conditions remains a pressing issue for maintaining the economic contribution of small businesses at a stable level.